SATISFACTION EVALUATION MODEL OF HIGH-LEVEL ATHLETES MANAGEMENT SYSTEM IN UNIVERSITIES OF SICHUAN PROVINCE OF CHINA - Tang Yudong; Mohd Salleh Aman; Lim Boon Hooi; Siswantoyo Siswantoyo (Jurnal Cakrawala Pendidikan, 2020)
The purpose of this study was to develop a questionnaire to measure satisfaction levels of Sichuan Province high-level athletes with their management systems using field investigation and mathematical statistics. Through the process of sorting and analyzing existing literature and in combination with the results of expert interviews, an ‘initial questionnaire’ consisting of 58 items and 6 dimensions was formed. As first steps, content validity and face validity of the questionnaire were tested. Then, SPSS 24 and Smart PLS 3 were used to carry out exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) respectively. After the unqualified items were deleted, a formal questionnaire comprising 49 items and 6 dimensions was ultimately formed. Reliability and validity tests demonstrated that the questionnaire had good internal consistency reliability and structural validity. By analyzing the structural model, it is found that the model has good prediction accuracy and prediction relevance, and the model fit is also good. Therefore, the evaluation model constructed in this study could be used as a tool for surveying satisfaction levels of Sichuan Province high-level athletes with their university management systems.